1987
DOI: 10.1007/bf00271139
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid cysts: diagnosis and treatment

Abstract: Twenty supratentorial and 10 infratentorial arachnoid cysts are reported. The patients were from 0 to 15 years of age. The commonest presenting symptoms in children were cranial enlargement, epileptic seizures, and psychomotor retardation. Neuroradiological evaluation included CT, metrizamide CT, cisternography, and angiography. Echography was performed in 5 newborns. Therapeutic criteria according to the clinical and neuroradiological findings are reviewed. Cystoperitoneal shunting in combination with ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Although shunting may offer less serious complications than a procedure requiring fenestration [19,20], the cooperative European study o f 285 cases o f arachnoid cysts [21 ] showed that cyst shunting necessitated a second surgical procedure more frequently and that the number o f reoperations is more than twice as high in those with initially shunted cysts. Other series have documented a high rate o f shunt-related complications in patients with C P shunts [18,20]. Shunt revisions are inevitable, and other serious complications can occur [28], In our series o f patients.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although shunting may offer less serious complications than a procedure requiring fenestration [19,20], the cooperative European study o f 285 cases o f arachnoid cysts [21 ] showed that cyst shunting necessitated a second surgical procedure more frequently and that the number o f reoperations is more than twice as high in those with initially shunted cysts. Other series have documented a high rate o f shunt-related complications in patients with C P shunts [18,20]. Shunt revisions are inevitable, and other serious complications can occur [28], In our series o f patients.…”
Section: Discussionmentioning
confidence: 77%
“…Some authors feel early surgical inter vention is warranted even for asymptomatic cases due to the possibility o f damage to developing structures [16,18]. Children with untreated cysts may have slowly pro gressive damage to adjacent neural structures [4] or be at increased risk o f an associated subdural hematoma or intracystic hemorrhage following minor head trauma [13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Leptomeningeal cysts form when a traumatic brain injury leads to extensive tissue loss and the gathering of fluid in the subarachnoidal space; they are clearly distinguishable from developmental arachnoid cysts, since there is no blocking of drainage. This is important because leptomeningeal cysts are clearly not present during language development, while arachnoid cysts have been demonstrated by ultrasound to occur before birth (Hidalgo et al, 1982;Locatelli et al, 1987;Sandler et al, 1988), although expansion may occur postnatally (Okumura et al, 1995).…”
Section: Subjectsmentioning
confidence: 99%
“…The options are no intervention in asymp tomatic patients, simple aspiration, burr hole and fenes tration, placing a shunt, ventriculocystostomy, cranio tomy with wide excision of the membrane and establish ment of communication with the subarachnoid cisterns [6,11,14,22,34,43,45], Some advocate not operating on asymptomatic cyst [8,13,19,43], some operating on all patients [27], Once the decision to operate has been made, radiological evaluation is employed to aid in the treatment [3,9,10,13,19,27,46,52]. Among the various surgical options available the merits and demerits of shunting and craniotomy have been strongly debated [27,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%